Chemical and Sensory Characteristics of Boranan Instant Chili Sauce with Different Coconut Milk Powder Concentration, Rice Flour, and Dry Grated Coconut - Mardhiyyah, Yunita; Puspitasari, Elsa; Rahmat, Anni (agriTECH, 2024)
Sego Boranan is a special food from Lamongan, East Java. They are cooked rice with various dishes flavored with a special chili sauce called Boranan sauce. Sauce consists of many ingredients with complex process production. Therefore, the study aimed to make Boranan sauce formulation coming from dry-based ingredients. Conversion of Boranan sauce recipe from fresh ingredients into powder preparations was carried out using water content data. Coconut milk powder, rice flour, and dry-grated coconut concentration was optimized within 9 sample formulations. All the samples were observed in chemical and sensory characteristics. The parameters observed included pH, proximate test, and preference test (color, aroma, texture, spices taste, and overall). The best formulas were compared with freshly made Boranan sauce. The pH and water content were not influenced significantly, in the other hand, the others (color, fat content, texture, aroma, taste, and overall sensory parameters) showed significant differences. Based on the preference test, high preference with a score of 7.91 acceptance value from a 10 scale was gained by both K2S1R1 and K1S2R1 samples. Although the panelist gave a “like” score, both samples showed significant sensory acceptance and proximate value differences from fresh-made Boranan sauce. The selected formula K2S1R1 was made from 4.5% dry grated coconut, 2.25% coconut milk powder, and 2.25% rice flour. The Rehydrated K2S1R1 sample had 70.7% (wet basis) water content, 1.4% ash content, 17.5% absorbent content, 0.5% protein content, and 8.8% carbohydrate content.